The Paraguay Reader : History, Culture, Politics - Nickson, Andrew; Lambert, Peter, 1948- (Book collections on Project MUSE., 2013)
This lively compilation of testimonies, journalism, scholarship, political tracts, literature, and illustrations conveys Paraguay's rich history and cultural heritage, as well as its struggles against underdevelopment, foreign intervention, poverty, inequality, and authoritarianism.